UJI DAYA HASIL TANAMAN PADI (Oryza sativa. L) MODEL JAJAR LEGOWO DI KOTA MADIUN - Sulistiyo Budi, Luluk; P.N., Ma’ruf (JURNAL AGRI-TEK, 2016)
Increased production of rice can be reached with planting prospective models are Jajar Legowo models. The research objective was to test the productivity of the land with the Jajar Legowo Model in Madiun. Method of the research was used a random block design in lowland Banjarejo village Taman Madiun In the season first planting in 2015. The treatment models Jajar Legowo used 2: 1, 4: 1 with control (22cmx22cm). Results of the test showed not significant difference in height plant parameters, number of productive tiller, fresh and dry weight stover. But showed significant differences in the parameters of dry unhusked, the average value of the highest achieved models Legowo row 2 : 1 of 7.4 tons / ha.KeyWords : production, Planting Model , jajar legowo, field paddy